The Pacific cupped oyster Crassostrea gigas : a species introduced in Europe for aquaculture in the 70's to become invasive in the late 90's - Miossec, Laurence; Goulletquer, Philippe (5th International Conference on Marine Bioinvasions, 2007)
The Pacific oyster Crassostrea gigas: from an introduced species for aquaculture to an invasive species for the ecosystem Miossec L. and Goulletquer Ph. The Pacific oyster Crassostrea gigas has been introduced worldwide for aquaculture purposes since the beginning of the last century. In most of the countries the species established broadly, emphasizing its ability to adapt to a wide range of environmental conditions. In Europe the Pacific oyster was massively introduced in the 1970s especially into France after mass mortalities of the Portuguese oyster Crassostrea angulata affected by a viral disease. Good environmental conditions in some French areas on the Atlantic coast induced successful recruitments in the following years. The population became established in the mid 70's. Illegal introductions in 1966 in Marennes Oleron were suspected to be the vector of the disease which affected the Portuguese oyster. This situation emphasized the risk of introducing unwanted organisms and disease agents when transplanting shellfish stocks without any precaution. Recent published studies demonstrated that Crassostrea gigas has taking advantage of last warm summers to expand northwards into new areas. Increases in oyster abundance were simultaneously registered in the newly colonized sites. This situation has been observed in France, UK, Germany and Netherlands but also in Norway since the mid of the 90's. The dynamics of oyster population is clearly related to recruitment success. First results underlined that this species is acting as an invader due to its extensive recruitment. The species compete for space with mussels populations. But whole negative ecological consequences are still under investigation. Moreover the colonisation of new areas by Crassostrea gigas involves social and economical consequences. Some of them could be beneficial as for example the development of new spat harvesting areas for shellfish industry. Others could be detrimental for oyster culture due to trophic and spatial competition between wild and cultured molluscs.